The Effect of the Perceived Organizational Climate on Job Burnout According to the Moderating Role of Social Support in the Employees of Selected Health Centers in Arak City - Atefeh Nobakht; Azita Salarian; Nader Khalesi (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2024)
Introduction: In a stressful work environment, individuals experience burnout; meanwhile, social support helps to reduce burnout. Therefore, the current research has investigated the effect of organizational climate on the burnout of employees of selected healthcare centers in Arak City, considering the moderating role of social support in 2023. Methods: The current research is applied, exploratory, and developmental in terms of purpose. Random sampling and based on Cochran's formula from 134 healthcare workers working in the health center, the questionnaire was completed. Demographic information forms, Maslach's (1993) job burnout questionnaire, Halpin and Kraft's (1963) organizational climate questionnaire, and Zimmet's (1988) perceived social support questionnaire were used to collect data. The results of model structure reliability tests, Cronbach's alpha values, composite reliability values, and rho_a, which indicate the internal correlation of questions of a variable within the model, are higher than 0.7 and have acceptable structure reliability. All the values of the HTMT index were less than the permissible value of 0.9 and were at a satisfactorylevel. Consequently, this test also confirmed the divergent validity. Results: The results with P > 0.001 and a 99% confidence level of the organizational atmosphere had an inverse effect on emotional burnout and depersonalization and directly impacted individual success. The perceived social support variable did not have a moderating role on the causal relationship of organizational climate with emotional burnout and depersonalization and its direction was reversed. However, it had a strengthening role in individual success and direct direction. In other words, people with more social support have more powerful personal success and vice versa. Conclusions: Organizational climate is one of the variables of job burnout, and people with higher social support have less job burnout. Therefore, it is suggested that managers conduct in-service training focusing on the components of job burnout and perceived organizational climate. In addition, friendly relations should be established with employees to increase social support, and rewards and welfare measures should be granted.